1999
DOI: 10.1093/jat/23.6.490
|View full text |Cite
|
Sign up to set email alerts
|

Benzodiazepines in Miami-Dade County, Florida Driving Under the Influence (DUI) Cases (1995-1998) with Emphasis on Rohypnol(R): GC-MS Confirmation, Patterns of Use Psychomotor Impairment, and Results of Florida Legislation

Abstract: Benzodiazepines are central nervous system depressant drugs often detected in biological samples from driving under the influence (DUI) offenders. They are associated with marked psychomotor impairment and represent up to 20% of all Miami-Dade County, Florida DUI urine samples analyzed in our laboratory annually. Flunitrazepam emerged in the mid-1990s as an illegal drug in the U.S. that was predominantly abused recreationally and associated with sexual assaults. Immunoassays for benzodiazepines do not discrimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…It is available in tablets containing 0.5 mg, 1 mg, and 2 mg clonazepam under the trade names Klonopin, Clonex, Iktorivil, and Rivotril. In a previously mentioned paper, Raymon et al reported a significant rise in clonazepam involvement in DUI cases in Florida after 1998 [16].…”
Section: Drug-facilitated Sexual Assaultmentioning
confidence: 96%
See 1 more Smart Citation
“…It is available in tablets containing 0.5 mg, 1 mg, and 2 mg clonazepam under the trade names Klonopin, Clonex, Iktorivil, and Rivotril. In a previously mentioned paper, Raymon et al reported a significant rise in clonazepam involvement in DUI cases in Florida after 1998 [16].…”
Section: Drug-facilitated Sexual Assaultmentioning
confidence: 96%
“…The authors of this study noted that 10% of voluntary users reported subsequent physical or sexual victimization. In another paper, Raymon et al reported significant involvement of flunitrazepam (among other benzodiazepines) in driving under the influence cases in South Florida between 1995 and 1998 [16]. Rohypnol tablets are smuggled into the US (mainly from Mexico) and sold with street names like roofies, rophies, roopies, rib, rope, pappas, peanuts, pastas, forget pills, ro-shays, roaches, and roche 2 [15].…”
Section: Drug-facilitated Sexual Assaultmentioning
confidence: 99%
“…Immunoassays for benzodiazepines do not discriminate between individual drugs, and the metabolite of fl unitrazepam (7 -aminofl unitrazepam) may react poorly with certain immunoassay reagents causing false -negative result (20) . Flunitrazepam (Rohypnol) is a benzodiazepine drug not approved for use in the United States.…”
Section: Drugs Not Detected In Drugs Of Abuse Testing Panelsmentioning
confidence: 99%
“…32 In the United States importation of flunitrazepam was banned 1996, but it is still available and popular in Europe and Latin America. 37 Clonazepam also is sold under the street name of "roofies" with clinical effects quite similar to flunitrazepam. The manufacturer has recently reformulated the drug to give a blue color when dissolved in clear drinks and to cause haziness in colored beverages.…”
Section: Cocainementioning
confidence: 99%